The Development of a Cognitive Test on Exercise Physiology for Exercise and Sports Science College Students - Arroyo, Julia Pearl (Journal of Interdisciplinary Perspectives, 2025)
Future exercise and sports science professionals must master human physiological concepts and their applications to be effective in their fields. The education of aspiring professionals in exercise and sports science requires quality assessment methods, from which results serve as a basis for educational and training programs. To ensure coherence with the program objectives of academic institutions and industry standards, the use of well-developed cognitive tests is imperative. This study aimed to develop a cognitive written test for an introductory course in Exercise Physiology for use in an Exercise and Sports Science program. Eighty sports science students participated in the development of the cognitive test. The constructed forty-item multiple-choice test had a Cronbach’s alpha of 0.73, indicating an “acceptable” internal consistency. Item-analysis results showed that 39 out of the 40 items had acceptable item difficulty levels, with a good combination of easy-desirable-difficult items. However, only 15 out of the 40 items were selected for retention, as 25 items were classified as having negative to poor item discrimination. The test development process entailed careful planning, pre-construction conceptualization, and a multi-step process, from identifying the test's purpose and constructing the table of specifications to item analysis and field testing. This study highlights the importance of test improvements and regular evaluation of curriculum assessment tools.